Minor actinides transmutation in pressurized water reactors. 2. Using uranium and thorium fuel to burn minor actinides in a system with several VVER reactors - Gleb W. Karpovich; Yuri A. Kazansky; Nikita D. Vasechkin; Kirill A. Bakhantsov (Nuclear Energy and Technology)
There is currently a consensus among the scientific and engineering community regarding the solution to the problem of minor actinides (MAs) formed in the process of nuclear power operation: MAs need to be converted to fission products during burnup in power reactors. Fast neutron reactors (BN, BREST) and molten salt reactors (MSR) are considered largely to this end. Despite the advantages of using fast reactors, there are no currently power unit designs with BN or BREST reactors available for commercial operation. The possibility of using VVER reactors for this purpose is rarely covered in scientific literature, despite the fact that the technology of light water reactors has long been mastered, and preparing a VVER-based MA burner reactor is technically simpler than on the basis of a pilot commercial BN technology or BREST or MSR reactors at different R&D stages. In the previously published first part of the study by Kazansky and Karpovich 2022, the fuel cycle for VVER reactors was investigated: minor actinides obtained during reactor operation were extracted from spent nuclear fuel and added to fresh fuel for the same reactor. It has been found that implementing this cycle and bringing the concentration of MAs up to 4 wt. % makes it possible to reduce the amount of minor actinides produced in the VVER reactor by a factor of 8, and without a loss in the NPP unit power generation. This paper investigates, based on an idea of closing the fuel cycle in terms of minor actinides, the relationship between the MA burnup depth in a VVER-1200 reactor and the enrichment of fresh fuel, the dynamics of unloaded heavy nuclei, and the amount of MAs in additionally loaded fuel. Under investigation are two types of additionally loaded fuel with oxides of minor actinides added to it: based on enriched uranium dioxide or a mixture of (1 – x) 232ThO2+x (96% UO2) (Kazansky et al. 2023). At the same time, the number of heavy nuclei in fuel does not change when there is a change in the number of loaded MA nuclei, which is measured in the number of the VVER-1200 reactors “served” (the mass of accumulated MA nuclei is about 1% and is removed annually from spent fuel). The number of minor actinides entering fuel is kept at a level that allows having a reactivity margin for the reactor operation at a power of over 2% before the annual refueling. Calculations were undertaken using a fuel assembly model with fuel elements broken down into a number of groups with different fuel burnup depths to simulate the actual loading of the reactor core. This model makes it possible to avoid the power peaking effects and give an answer about the neutronic characteristics of the fuel cycle involving MAs. The calculations made it possible to make a number of important conclusions: more refueling cycles lead to a dynamic equilibrium taking place between the minor actinide amounts loaded and burnt; the number of the reactors served is directly proportional to the enrichment of the make-up fuel and a 20% UO2 enrichment makes it possible to serve up to 23 VVER-1200 reactors, while using 80% 232ThO2 + 20% (96% UO2) fuel allows 17 VVER-1200 reactors to be served; using MAs extracted from SNF with a burnup of 20 to 50 MW*day/kg leads to the MA composition effect on the reactivity balance being within 4 to 5 βeff.